2011
DOI: 10.1002/rmv.699
|View full text |Cite
|
Sign up to set email alerts
|

The molecular and pathophysiological implications of hepatitis B X antigen in chronic hepatitis B virus infection

Abstract: Hepatitis B virus is considered one of the most significant environmental carcinogens in humans. Because the mechanisms of HBV replication and the development of hepatocellular carcinoma (HCC) are partially known, HBV-associated pathogenesis remains a challenge to increase its understanding. Evidence suggests that the regulatory protein hepatitis B virus X (HBx) mediates the establishment and maintenance of the chronic carrier state. HBx is a multifunctional and potentially oncogenic protein that is conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 141 publications
(190 reference statements)
3
42
0
Order By: Relevance
“…[30][31][32][33][34] Indeed, HBx can alter the expression patterns of apoptosis-related genes to promote cell survival and persistence of the carrier state. 6,7 In the current study, we found that TNFRSF10B degradation induced by HBx leads to the downregulation of its cell surface expression with no effect on the expression of other apoptosis-related proteins such as CASP8, FADD, BIRC3/cIAP2 (baculoviral IAP repeat containing 3), CFLAR/c-FLIP (CASP8 and FADD like apoptosis regulator), and MCL1 (BCL2 family apoptosis regulator) (Fig. S3).…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…[30][31][32][33][34] Indeed, HBx can alter the expression patterns of apoptosis-related genes to promote cell survival and persistence of the carrier state. 6,7 In the current study, we found that TNFRSF10B degradation induced by HBx leads to the downregulation of its cell surface expression with no effect on the expression of other apoptosis-related proteins such as CASP8, FADD, BIRC3/cIAP2 (baculoviral IAP repeat containing 3), CFLAR/c-FLIP (CASP8 and FADD like apoptosis regulator), and MCL1 (BCL2 family apoptosis regulator) (Fig. S3).…”
Section: Discussionmentioning
confidence: 58%
“…12,13,24 The essential function of HBx in HBV replication and liver inflammation is well known. 6,7 HBx is a multifunctional protein that affects multiple events in infected cells, including signal transduction, proteasome activity, cell proliferation, and apoptosis. 6,7,[25][26][27][28][29] Numerous lines of evidence suggest that HBx contributes to protection of infected hepatocytes from immune-mediated destruction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations